6.177 Problems 17601 to 17700

Table 6.353: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

17601

\[ {}y^{\prime \prime }-9 y^{\prime }+9 y = 0 \]

17602

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

17603

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

17604

\[ {}9 y^{\prime \prime }-24 y^{\prime }+16 y = 0 \]

17605

\[ {}4 y^{\prime \prime }+9 y = 0 \]

17606

\[ {}4 y^{\prime \prime }+9 y^{\prime }-9 y = 0 \]

17607

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

17608

\[ {}y^{\prime \prime }+4 y^{\prime }+\frac {25 y}{4} = 0 \]

17609

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

17610

\[ {}y^{\prime \prime }+16 y = 0 \]

17611

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

17612

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

17613

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

17614

\[ {}6 y^{\prime \prime }-5 y^{\prime }+y = 0 \]

17615

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

17616

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

17617

\[ {}y^{\prime \prime }+3 y^{\prime } = 0 \]

17618

\[ {}y^{\prime \prime }+y = 0 \]

17619

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

17620

\[ {}y^{\prime \prime }+6 y^{\prime }+3 y = 0 \]

17621

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

17622

\[ {}2 y^{\prime \prime }+y^{\prime }-4 y = 0 \]

17623

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

17624

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

17625

\[ {}4 y^{\prime \prime }-y = 0 \]

17626

\[ {}a \,x^{2} y^{\prime \prime }+b x y^{\prime }+c y = 0 \]

17627

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0 \]

17628

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

17629

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+\frac {5 y}{4} = 0 \]

17630

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }-6 y = 0 \]

17631

\[ {}x^{2} y^{\prime \prime }-2 y = 0 \]

17632

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0 \]

17633

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }+4 y = 0 \]

17634

\[ {}2 x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

17635

\[ {}2 x^{2} y^{\prime \prime }+x y^{\prime }-3 y = 0 \]

17636

\[ {}4 x^{2} y^{\prime \prime }+8 x y^{\prime }+17 y = 0 \]

17637

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0 \]

17638

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+5 y = 0 \]

17639

\[ {}y^{\prime \prime }+2 y = 0 \]

17640

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 0 \]

17641

\[ {}m y^{\prime \prime }+k y = 0 \]

17642

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 3 \,{\mathrm e}^{2 t} \]

17643

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \sin \left (2 t \right ) \]

17644

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = -3 t \,{\mathrm e}^{-t} \]

17645

\[ {}y^{\prime \prime }+2 y^{\prime } = 3+4 \sin \left (2 t \right ) \]

17646

\[ {}y^{\prime \prime }+9 y = t^{2} {\mathrm e}^{3 t}+6 \]

17647

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \,{\mathrm e}^{-t} \]

17648

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 2 \,{\mathrm e}^{t} \]

17649

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 2 \,{\mathrm e}^{-t} \]

17650

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]

17651

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 16 \,{\mathrm e}^{\frac {t}{2}} \]

17652

\[ {}2 y^{\prime \prime }+3 y^{\prime }+y = t^{2}+3 \sin \left (t \right ) \]

17653

\[ {}y^{\prime \prime }+y = 3 \sin \left (2 t \right )+t \cos \left (2 t \right ) \]

17654

\[ {}u^{\prime \prime }+w_{0}^{2} u = \cos \left (w t \right ) \]

17655

\[ {}y^{\prime \prime }+y^{\prime }+4 y = 2 \sinh \left (t \right ) \]

17656

\[ {}y^{\prime \prime }-y^{\prime }-2 y = \cosh \left (2 t \right ) \]

17657

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 2 t \]

17658

\[ {}y^{\prime \prime }+4 y = t^{2}+3 \,{\mathrm e}^{t} \]

17659

\[ {}y^{\prime \prime }-2 y^{\prime }+y = t \,{\mathrm e}^{t}+4 \]

17660

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 3 t \,{\mathrm e}^{2 t} \]

17661

\[ {}y^{\prime \prime }+4 y = 3 \sin \left (2 t \right ) \]

17662

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 4 \,{\mathrm e}^{-t} \cos \left (2 t \right ) \]

17663

\[ {}y^{\prime \prime }+3 y^{\prime } = 2 t^{4}+t^{2} {\mathrm e}^{-3 t}+\sin \left (3 t \right ) \]

17664

\[ {}y^{\prime \prime }+y = t \left (\sin \left (t \right )+1\right ) \]

17665

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{t} \cos \left (2 t \right )+{\mathrm e}^{2 t} \left (3 t +4\right ) \sin \left (t \right ) \]

17666

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 3 \,{\mathrm e}^{-t}+2 \,{\mathrm e}^{-t} \cos \left (t \right )+4 \,{\mathrm e}^{-t} t^{2} \sin \left (t \right ) \]

17667

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 2 t^{2}+4 t \,{\mathrm e}^{2 t}+t \sin \left (2 t \right ) \]

17668

\[ {}y^{\prime \prime }+4 y = t^{2} \sin \left (2 t \right )+\left (6 t +7\right ) \cos \left (2 t \right ) \]

17669

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{t} \left (t^{2}+1\right ) \sin \left (2 t \right )+3 \,{\mathrm e}^{-t} \cos \left (t \right )+4 \,{\mathrm e}^{t} \]

17670

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 t \,{\mathrm e}^{-t} \cos \left (2 t \right )-2 t \,{\mathrm e}^{-2 t} \cos \left (t \right ) \]

17671

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 2 \,{\mathrm e}^{-t} \]

17672

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = \ln \left (x \right ) \]

17673

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+5 y = x \]

17674

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 3 x^{2}+2 \ln \left (x \right ) \]

17675

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = \sin \left (\ln \left (x \right )\right ) \]

17676

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} t & 0\le t \le \pi \\ \pi \,{\mathrm e}^{-t +\pi } & \pi <t \end {array}\right . \]

17677

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = \left \{\begin {array}{cc} 1 & 0\le t \le \frac {\pi }{2} \\ 0 & \frac {\pi }{2}<t \end {array}\right . \]

17678

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} A t & 0\le t \le \pi \\ A \left (2 \pi -t \right ) & \pi <t \le 2 \pi \\ 0 & 2 \pi <t \end {array}\right . \]

17679

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 2 \cos \left (w t \right ) \]

17680

\[ {}y^{\prime \prime }+y = 2 \cos \left (w t \right ) \]

17681

\[ {}y^{\prime \prime }+y = 3 \cos \left (w t \right ) \]

17682

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (\frac {t}{4}\right ) \]

17683

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (2 t \right ) \]

17684

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (6 t \right ) \]

17685

\[ {}y^{\prime \prime }+y+\frac {y^{3}}{5} = \cos \left (w t \right ) \]

17686

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{5}+y+\frac {y^{3}}{5} = \cos \left (w t \right ) \]

17687

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 2 \,{\mathrm e}^{t} \]

17688

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 2 \,{\mathrm e}^{-t} \]

17689

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]

17690

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 16 \,{\mathrm e}^{\frac {t}{2}} \]

17691

\[ {}y^{\prime \prime }+y = \tan \left (t \right ) \]

17692

\[ {}y^{\prime \prime }+4 y = 3 \sec \left (2 t \right )^{2} \]

17693

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 t}}{t^{2}} \]

17694

\[ {}y^{\prime \prime }+4 y = 2 \csc \left (\frac {t}{2}\right ) \]

17695

\[ {}4 y^{\prime \prime }+y = 2 \sec \left (2 t \right ) \]

17696

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{t}}{t^{2}+1} \]

17697

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = g \left (t \right ) \]

17698

\[ {}y^{\prime \prime }+4 y = g \left (t \right ) \]

17699

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 2 t^{3} \]

17700

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }+y = t^{2} {\mathrm e}^{2 t} \]